Tunable graphene-based Q-switched erbium-doped fiber laser using fiber Bragg grating - Ahmad, Harith; Zulkifli, M.Z.; Muhammad, F.D.; Zulkifli, Ahmad Zarif; Harun, Sulaiman Wadi (Taylor & Francis, 2013)
A graphene-based Q-switched erbium-doped fiber laser (EDFL) with a tunable fiber Bragg grating (TFBG) acting as a wavelength tuning mechanism is proposed and demonstrated. The proposed setup utilizes a newly-developed ‘ferrule-to-ferrule transfer’ technique to obtain a single graphene layer that allows for Q-switch operation in the EDFL using a highly doped-gain medium. A TFBG is used as a wavelength tuning mechanism with a tuning range of 10 nm, covering the wavelength range from 1547.66 nm to 1557.66 nm. The system has a wide repetition rate range of over 206.613 kHz from 1.387 kHz to 208.000 kHz with pulse durations of between 94.80 μs to 0.412 μs. The laser output is dependent on the pump power, with energy per pulse of 4.56 nJ to 16.26 nJ. The system is stable, with power and wavelength variations of less than 0.47 dBm and 0.067 nm. The output pulse train is free from self-mode locking and pulse jitters.